2007 40th Annual Hawaii International Conference on System Sciences (HICSS'07) 2007
DOI: 10.1109/hicss.2007.92
|View full text |Cite
|
Sign up to set email alerts
|

Audio vs. Chat: The Effects of Group Size on Media Choice

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
0
4
0
3
Order By: Relevance
“…For the first conscious form of audio stimulus, we note that high-quality voice chat which reasonably captures the nuances of verbal communication is now generally available [Short et al 1976;Lober et al 2007;Wadley et al 2009]. In this regard, the sense of hearing is somewhat ahead of sight in capturing avatar expression and interaction.…”
Section: Realismmentioning
confidence: 95%
“…For the first conscious form of audio stimulus, we note that high-quality voice chat which reasonably captures the nuances of verbal communication is now generally available [Short et al 1976;Lober et al 2007;Wadley et al 2009]. In this regard, the sense of hearing is somewhat ahead of sight in capturing avatar expression and interaction.…”
Section: Realismmentioning
confidence: 95%
“…[16]). Taking a closer look at the usage of rich communication media smaller groups seem to adjust better, while larger roups feel overburdened by rich media [37]. Furthermore Riopelle et al [45] found larger teams to have more difficulties in communicating than smaller teams using audio conferencing.…”
Section: Team Sizementioning
confidence: 97%
“…As a result, textual chat is preferred as a means to communicate in situations where players do not personally know each other [3]. Additionally, Lober et al [4] identified that textual chat is a more effective form of communication with larger team sizes in different settings, but voice seemed to be faster when teams had to make quick decisions [5]. However, there is little research on what is the more preferred and efficient form of communication in task-oriented MMOGs.…”
Section: Introductionmentioning
confidence: 99%